马来西亚南部独中生华语“拿”类手部动作动词的应用研究 = A study of the use of the Mandarin Chinese taking verbs (NA “拿”verbs) by independent school students in Southern Malaysia - 陈秀君 Chin, Siew Chien (2014)
马来西亚华语是在没有普通话的基础上发展起来的，它是基于官方政策和族群接触的驱使而在异地传播的过程中、在变与不变之间孕育出语体混杂的独特性。这足以预见马来西亚华语在“标准华语”以外所具备的地域性和变异性。本论文集中研究马来西亚华语中的“拿”类手部动作单音节近义动词，以南马区三所独中（新山宽中古来分校、峇株新文龙中华中学和麻坡中化中学）的 90 位学生为被试，通过实验一“填一填”，考察被试在开放语境下对这类动词使用的准确度和这类词汇掌握的丰富度；和实验二“选一选”，考察被试在封闭语境下对这类近义动词的语义理解和语义辨析能力，探讨他们理解辨析和普遍使用的特点，以及认知发展和习得成效的内容。 全篇论文共分为五章，主要从语言习得、语言认知和语言本土性三个角度去切入考察。第一章概述研究意义及前人已累积的研究成果，同时梳理独中的历时发展及独中华语教育中近义词项目的教学比例。第二章交待研究假设，同时确定被考察的独中、“拿”类手部动作单音节动词和被试范围，并介绍两项实验的设题凭据、使用材料和测试方法。第三章检视被试对“拿”类手部动作单音节近义动词的理解、辨析和使用结果。通过对被试的使用语料和理解测试进行量化，辅以统计检验学年段、方言使用率和地区的变项影响，整理出“以一概全”、“一物多拿”、认知“拿”和“拿”类手部动作动词中方言借词的生成和使用这几种显著表现的形式，并指出 11 个“拿”类手部动作单音节动词在近义理解和辨析方面有明显掌握不足和模糊认知的现象。第四章将量化结果置入非任意性的脉络中，不仅分析“以一概全”必然形成的原因和无标记成分[手] + [持/取] + [物体]对此聚焦现象的认知影响，同时说明“语言具身性”、“语言范畴化”和“语言描摹性”在启动“V（“拿”类手部动作）+N”结构、“一物多拿”现象和认知“拿”机制上都扮演着举足轻重的角色。除外还着眼南马区语言环境中大量存在方言借用的现象，观察 “词素移借”在方言介入华语之际具体的变异关系。而最后一章是结论，除了归纳各章要点之外，也尝试从“拿”类手部动作单音节近义动词研究中反思对语言与认知、语言与社会、马来西亚华语研究等方面仍可开拓的空间。 这项研究是根据社会语言学和认知语言学的理论运用实证调查研究的方法做了一项特定领域词汇习得的研究。希望本研究的结果会让我们更了解多语环境和语言接触如何促成标准华语产生区域变异的特征。This thesis is a study of the use of the Mandarin Chinese taking verbs (Na“拿”verbs) by Malaysian Chinese students, whose native language is Mandarin Chinese and who were studying in the independent school, where the medium of instruction was Mandarin Chinese, in Malaysia. The thesis consists of five chapters. Chapter One is an introduction, which includes our research objectives and literature review. An introduction of the curriculum of Chinese language teaching, especially the teaching and learning of the verb category in the same lexical domain of our study in independent schools in Malaysia is also reviewed. Chapter Two introduces our hypotheses, the scope of our study, and research methods applied. The results of the study are shown in Chapter Three. Four types of the participants’ distinctive usage, namely, the overgeneralization in use of one taking verb, one patient object associated with multiple taking verbs, the cognitive schema applied to the semantic understanding of the taking verbs, and some loanwords in the Malaysian Mandarin from Southern Chinese Dialects. The experiments on the 11 taking verbs showed imperfect learning, i.e. the deficiency of acquiring the accurate meanings of a specific verb. Chapter Four is the discussion and analysis, in which the focus was on the phenomenon of the overgeneralization in the participants’ use of one taking verb in many different contexts and cognitive schema applied to their semantic understanding of the taking verbs. Factors that caused the overgeneralization and cognitive schema were assumed to be due to the participants’ object categorization and language imitations which might also affect the participants’ verb choices as well as the unmarkeness of the [hand]+[Na]+[object]. Furthermore, some other features of the Mandarin spoken in Malaysia, such as the ‘morpheme borrowing’, etc., which are believed to be the results of contact between Mandarin and Southern Chinese dialects, are illustrated as well. Chapter five is the conclusion and a brief statement of directions for future research. The results show that the sociolinguistic settings in Malaysia brought about different variabilities of the use of the 11 taking verbs tested and that although the Mandarin-speaking students used Mandarin as standard Chinese, their usage in general illustrated regional features of the language use. Overall, the study has shown the indigenousness of the Mandarin spoken in Malaysia from the perspectives of language acquisition and cognition.